Behavioral and institutional determinants of PPE use among nurses during the COVID-19 outbreak - Namira, Bunga Azalea; Nurfikri, Ari (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Health services as the sector most affected by this situation must also prepare to face the Covid-19 pandemic. Hospitals must start thinking about the steps to be taken to continue treating Covid-19 patients but at the same time also provide services to general patients with minimal risk of transmission, so it is called a balancing act. Methods: This study was obtained by distributing questionnaires to respondents to determine the description of knowledge, attitudes, completeness, comfort, and supervision of respondents, namely nurses at Grha Permata Ibu Hospital. Findings: The gender characteristics of nurses at Grha Permata Ibu Hospital are dominated by female nurses as many as 75 people (92.4%) while male nurses as many as 6 people (7.6%). The majority of nurses at Grha Permata Ibu Hospital completed their last education at DIII as many as 65 people (79.7%), and Bachelor Degree+Ners as many as 16 people (20.3%). The average length of work of nurses at Grha Permata Ibu Hospital is 1-10 years, which is as many as 55 people (68.8%). The lowest length of work as a nurse is 1 month and the highest is 25 years. The level of knowledge regarding compliance with the use of PPE among nurses at Grha Permata Ibu Hospital is at a good level of knowledge, which is as many as 76.3% and less good, which is as many as 23.8%. Conclusion: People who are vulnerable to infection are people who are close to patients or nurses who treat Covid-19 patients. Nurses are currently at significant risk of contracting the infection so it is important for nurses to protect themselves from exposure to the virus. This is what makes nurses and doctors feel unsafe in using PPE because in providing care to patients, the corona virus has been proven to survive in the environment and will be a potential source of infection for hours or even days. Novelty/Originality: This study reveals that the most common reason for not using PPE among nurses was the unavailability of PPE—an operational gap that is often overlooked in previous research on PPE compliance in hospital settings during the pandemic.